Seasonal Fluctuations in the Population of Eurytoma settitibia Gahan (Eurytomodae : Hymenoptera) , a Potential Stem Gall Chalcid of Khejri (Prosopis cineraria Linn.) in Rajasthan - Ahmed, S. T.; Kumar, Shivesh (Indian Forester, 2004)
Seasonal variation in the population of stem gall chalcid , E. settitibia was snrveyed and studied in a young stand of P. cineraria in the experimental field during 1998-1999. Census was carried out for five stages i.e. (i) potential eggs , (ii) newly hatched larvae , (iii) larvae in galls , (iv) pupae in galls and (v) emcrging adults. Population density of potential eggs was recorded to he 18659 ± 968 eggs per m3. The population density has been calculated based on the density of 67 females and the mean fecundity per female. The population density of newly hatched larvae was 3621±39 per m3. Out of the density of total eggs deposited , only 61.93% larvae were hatched. The major mortality factor of the newly hatched larvae was observed to be the failure of hatched larvae to penetrate into the cambial layers of the growing shoots. The population density of first instar larvae in galls was 2598±98 individuals per m3. , and about 64% of newly hatched larvae died before the formation of gall. The population density of pupae in galls was 1785 ±360 per m3. , and 31.2% mortality of larvae was observed inside the emerging galls. A group oflarvae live together in a single gall and the number of larvae per gall ranged from 21-268 with a mean of 129.9 larvae per gall. Statistical correlations between egg clusters and total eggs; egg hatched and total eggs laid and larval mortality and total eggs , indicated that these parameters are positively correlated with each other under similar conditions of abiotic factors. The highest population of adults (68.82 adults per gall) was recorded in the second fortnight of August when the optimum ranges of abiotic factors i.e. temperature (23.5 to 34.5°C) and relative humidity (60 to 71 %) were available in the field whereas the minimum number (2.95 adults per gall) was observed in the month of December.